PENGARUH KUALITAS PELAYANAN DAN KESELAMATAN PASIEN TERHADAP KEPUASAN PASIEN KLINIK PRATAMA SEHATI KABUPATEN BANDUNG - Hendra Permadi; Winna Sarikusumaningtyas; Sugeng Prayetno (Bajang Institute, 2026)
High-quality healthcare services are one of the main indicators of the success of primary healthcare facilities in meeting community healthcare needs. Along with increasing public awareness regarding healthcare quality, primary clinics are expected not only to provide efficient and responsive healthcare services but also to ensure patient safety throughout the healthcare process. Patient safety is an integral component of healthcare quality that directly influences patient trust and satisfaction. This study aimed to analyze the influence of service quality and patient safety on patient satisfaction at Sehati Primary Clinic, Bandung Regency. This study employed a quantitative survey approach involving 60 respondents selected through Slovin’s Formula. Data were collected using a structured questionnaire measured with a five-point Likert scale. Multiple linear regression analysis was performed using SPSS. The results indicate that service quality has a positive and significant effect on patient satisfaction (β = 0.460; p < 0.001). Patient safety also has a positive and significant effect on patient satisfaction (β = 0.397; p = 0.001). Simultaneously, both variables significantly affect patient satisfaction (F = 41.045; p < 0.001), with an R-square value of 0.590, indicating that 59% of patient satisfaction can be explained by service quality and patient safety. These findings suggest that improving healthcare service quality and strengthening patient safety culture are essential strategies for increasing patient satisfaction in primary healthcare facilities.